Shakespeare's Sublime Pathos - Sell, Jonathan P. A. (Taylor & Francis Group, 2021)
Cover – Endorsement Page – Half Title – Series Page – Title Page – Copyright Page – Dedication – Table of Contents – Acknowledgements – A Note on Conventions – Abbreviated Titles of Shakespeare's Works – Introduction – Aims and
Description based on publisher supplied metadata and other sources
Keywords: Shakespeare; William; -1564-1616-Criticism and interpretation; Sublime; The; in literature; Pathos in literature; Electronic books